La salud sexual - reproductiva y el embarazo precoz en adolescentes del Colegio Galo Plaza Lasso en el tercer año de bachillerato del cantón Echeandia, durante el periodo julio a diciembre del 2013 - Guevara Guamán, Geovana Marilú (2014)
The importance of knowledge in sexual and reproductive health in adolescents is an important factor in the incidence of pregnancy in girls, early relations, being one of the main causes lack of same education located in the poor quality of education, the social and economic problems, the influence of the media, the hostile social environment in which they operate and technological advancementsthey have directly influenced the life and sexual behaviour of adolescents. Educational deficiencies teenagers and the family on Sexual Health and reproductive gets weak knowledge and it becomes a factor in society resulting to our teens begin with an unwanted pregnancy. By which it is necessary to coordinate with various institutions as one of them the College National Galo Plaza Lasso of the Canton Echeandía to undertake the teen pregnancy prevention campaigns in order to promote sexual and reproductive health, knowledge about contraceptive methods, duties and rights of adolescents for their sexuality, so it is very important that education comes from one's homeraising parents breaking taboos and myths, continuing in the establishments of education and integral work of health personnel to do so.